Review and evaluation of the codification of the plenary synod in Poland in the interwar period - Czarnowski, Robert (Prawo Kanoniczne, 2024)
The article addresses the topic of the codification of decisions of the first Polish plenary synod in Poland, which took place in 1936, highlighting its significance during the interwar period. The synod, through 151 decrees divided into fifteen chapters, tackled key issues related to liturgy related to liturgy, sacramental life, and church discipline. A significant point of analysis is the influence of the 1917 Code of Canon Law, which served as the foundation for the norms contained in the synodal decrees, contributing to the creation of a coherent legal system within the Polish Church.